Psychometric properties of the intercultural effectiveness scale in a sample of in-service Chilean EFL teachers - Klenner-Loebel, Maura; Gálvez-Nieto, José Luis; Beltrán Véliz, Juan Carlos; Ormazabal Astudillo, Carmen Gloria; Norambuena-Paredes, Ignacio (Frontiers in Psychology, 2026)
This study aims to validate the adaptation of the Intercultural Effectiveness Scale (IES) to the Chilean Spanish language context within a sample of 393 in-service Chilean EFL teachers. Intercultural effectiveness, a critical dimension of Intercultural Communication Competence (ICC), is essential for promoting culturally responsive pedagogy in diverse classrooms. The IES, comprising six factors—Behavioral Flexibility, Interaction Relaxation, Interactant Respect, Message Skills, Identity Maintenance, and Interaction Management—was analyzed using confirmatory factor analysis (CFA). The results confirmed the six-factor structure of the scale, with adequate fit indices. McDonald’s ω coefficients ranged from 0.608 to 0.723, indicating moderate reliability; however, values close to 0.60 reflect limited precision and suggest room for future improvement. Convergent validity was supported through correlations with the Multicultural Awareness Scale (MAS), particularly the Implicit Culture Awareness factor. Although positive correlations were identified, the Message Skills factor demonstrated non-significant correlations, suggesting potential areas for pedagogical improvement. This study highlights the relevance of IES as a tool for enhancing professional development programs that aim to foster ICC in teachers. The findings of this study have implications for curriculum design, intercultural training, and educational policies, particularly in culturally diverse contexts. Future research should focus on the longitudinal impacts of training on teachers’ intercultural effectiveness and on the predictive relationships between ICC and student learning outcomes.